The effects of water level shrinkage in the Lake Chad Basin on costs of production of local residents - Danna, Abba; Abbo, Bakari; Pare, Youssouf (International Journal of Applied Mathematical Research, 2017)
In this paper, we are interested at the modeling and numerical simulation of the impact of dewatering of Lake Chad on income riverrains, to help decision-makers to take the appropriate measures.But in these case, we use the dual of simplex method in order to minimizing the three "targets" populations production costs.Â